Zhaahirat Tahwiil al-Syafrah fi al-Muhaadatsah - Cahya Buana (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2012)
In all areas of life, human beings will not be separated from the language in the process of communication with each other. Everthing will go well as it can be arranged with the language associated with social conditions (sociolingusitic) is a very interesting study. This paper will discuss one of the objects of languages study, it's the code switching occurs in some forms of speech of speakers who speak Arabic and Indonesian. The author specialized in the analysis of the causes of code switching in five forms of conversations, namely a desire of speaker to demonstrate his proficiency of bilingual and trying to make the audience believe hismastery, the emotional expression, accelerating the delivery of messages, making the limit between jokes and serious conversation, continuityof using the mother tongue because it is easier, limiting the audience, keep he distance of social status, the awareness that the second languageis also a mother tongue, adopt the foreign sentence, and reinforce the speech.